Genetical basis of the plasticity of resource allocation in the Pacific oyster (Crassostrea gigas) - Ernande, Bruno; Haure, Joel; Degremont, Lionel; Bedier, Edouard; Boudry, Pierre (94th Annual Meeting of the National Shellfisheries Assocation, 2002)
Phenotypic and genetic correlations between fitness-related life-history traits - such as survival, growth and reproductive allocation - have to be considered to better understand selective processes, both in the wild and in breeding programs. Quantitative genetic experiments, based on nested half-sib mating designs, were perfomed in the Pacific oyster C. gigas (1) to estimate genetic variance and the response to selection and (2) to document phenotypic and genetic trade-offs between life history traits. Physiological trade-offs, i.e. plastcity of resource allocation, were shown to vary among genotypes. Genetic polymorphism was primarily observed for the the plasticity of reproductive effort. In addition, the degree of plasticity in reproductive effort appeared to be genetically correlated with mean survival. The signs of some signficant genetic correlations were found to reverse accross environments. These results could explain the maintenance of genetic polymorphism for the studied traits. These may help us to better understand the causes of summer mortalities in C. gigas juveniles, on which a national program recently started in France.